Ratcheting occurrence conditions of piping under sinusoidal excitations - Jinqi LYU (The Japan Society of Mechanical Engineers, 2020)
Ratcheting is one of the dominant failure modes under excessive earthquakes and may cause extreme failures of structures (e.g., collapse). We focused on clarifying the ratcheting mechanism of piping under sinusoidal excitations. Both finite element analyses and experiments were conducted on bent solid bars, which represented piping in this study. Seismic ratcheting occurred due to the combined effect of constant external compressive force and cyclic vibrations. The external compressive force acted as a load-controlled load. Vibrations were applied to provide the source of the dynamic load. Characteristics of vibrations between load-controlled and displacement-controlled properties were studied from the viewpoint of the frequency ratio of the forcing frequency to the natural frequency of the piping model. In addition, the influence of supports on the occurrence of ratcheting was also considered. The results showed that the resonance effect was evident in the piping model compared with the beam model due to the limited plastic area in the piping model. The vibration with a lower frequency had load-controlled characteristics. In contrast, the vibration with a higher frequency presented displacement-controlled properties. In terms of the occurrence of ratcheting, providing more supports sometimes increased the possibility of the occurrence of ratcheting under relatively higher forcing frequencies because more supports increased the natural frequency and decreased the frequency ratio.